CFD simulation of the hydrodynamics within an RVF module in laminar regime - Cheng Ming; Fillaudeau Luc; Schmitz Philippe (MATEC Web of Conferences, 2023)
The dynamic filtration module called Rotating and Vibrating Filtration (RVF) is a performant device for membrane fouling control and limiting the formation of cake layer. Indeed, it can generate strong shear stress at the membrane surface decoupled from the feeding flowrate. Moreover, the pressure fluctuation that takes place in the device is also beneficial to control membrane fouling. A CFD model has been validated in laminar regime from experimental measurements of velocity fields and pressure distribution inside the RVF. The boundary layer development at the walls were carefully studied to better explain the effects of the rotation speed and the viscosity on the spatial distribution and time variations of pressure and shear stress at the membrane surface. It appears that shear stress is more efficient than pressure to control membrane performances in laminar regime.